Effects of frequency of supplementation on performance of beef cows grazing winter pasture - Farmer, C.G.; Cochran, R.C.; Simms, D.D.; Klevesahl, E.A.; Wickersham, T.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty spring-calving Hereford × Angus cows grazing low-quality tallgrass-prairie forage during the winter of 1998 were fed a 43% crude protein supplement 2, 3, 5, or 7 days a week. Supplement was fed at 4 lb/head daily to cows supplemented daily. The other cows still received 28 lb per week but divided equally among feedings. Cumulative performance (measured by changes in body condition score and body weight) was slightly better with increased supplementation frequency. However, the magnitude of differences in body condition and body weight changes, even for the most extreme treatment comparisons, were relatively small.
Keywords: Beef; Forage; Supplementation; Frequency